STRESSAWAY: A DUAL-PURPOSE PORTABLE MASSAGER AND BLOOD PRESSURE MONITOR USING PNEUMATIC COMPRESSION - Patil Virbhadra Ravindranath; Patil Gururaj Chatursen; Swami Shivaraj Dayanand; Bhandekar Swapnil Prashant; Prof. Upadhe S. N. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This research proposes STRESSAWAY—a cost-effective, portable health device integrating oscillometric blood pressure monitoring with therapeutic intermittent pneumatic compression (IPC). Targeted at health-conscious individuals, the device automates arm cuff inflation/deflation to simultaneously measure blood pressure and deliver compression massage therapy. Extensive literature and component-level investigations informed the system’s dual-function design. The prototype, comprising an ESP32 controller, pressure sensor, air pump, and NIBP cuff, demonstrated reliable systolic/diastolic readings and noticeable muscle relaxation. The project confirms the feasibility of merging diagnostic and therapeutic functions in one unit, with future prospects for smart features like HRV tracking, app connectivity, and modular massage attachments.